New ways of developing agricultural technologies: The Zanzibar experience with participatory integrated pest management - Bruin, G.C.A.; Meerman, F. (CTA / WUR, 2001)
The project described in this book is an example of the successful adaptation of the farmer field school model developed by FAO for rice pest management. The project's success was based on the involvement of subsistence farmers in the development of new pest management methods.